2020
DOI: 10.1186/s12887-020-02421-1
|View full text |Cite
|
Sign up to set email alerts
|

Feature-driven classification reveals potential comorbid subtypes within childhood apraxia of speech

Abstract: Background Childhood apraxia of speech (CAS) is a neurodevelopmental disorder with heterogeneous communication and other comorbid manifestations. While previous studies have characterized speech deficits associated with CAS, few studies have examined variability in reading and language and/or other developmental comorbidities. We sought to identify comorbid subgroups within CAS that could be clinically relevant as well as genetically distinctive. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
(72 reference statements)
0
6
0
1
Order By: Relevance
“…Similar findings come from studies with different methodological approaches. Wren et al ( 2016 ) and Stein et al ( 2020 ) longitudinally studies children with SSD and found that week sucking and similar early fine motor coordination problems were important predictors of persistent and severe SSD.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings come from studies with different methodological approaches. Wren et al ( 2016 ) and Stein et al ( 2020 ) longitudinally studies children with SSD and found that week sucking and similar early fine motor coordination problems were important predictors of persistent and severe SSD.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid disorders of motor planning are highly relevant to communication development in NDDs, since they are more closely linked with overall language and literacy development than structural disorders, dysarthria, or stuttering and put children at risk for later language and literacy challenges even in those cases where the initial disorder has resolved [ 46 , 56 , 65 , 85 , 90 ]. Recent comorbidity studies have shown that children with disorders of motor planning plus other NDDs experience more severe communication profiles than children without such comorbidity [ 10 , 14 , 16 , 43 ].…”
Section: Developmental Speech Disordersmentioning
confidence: 99%
“…Studying a large cohort of children with LI and SSD, Lewis et al [40] found that the severity of language impairment, rather than that of the speech sound disorder, was most predictive of the severity of inattention and hyperactivity/impulsivity. In a more recent study on a small group of children with CAS and comorbid ADHD, LI and a reading disability, Stein et al [25] reported that ADHD was associated with more severe speech and language profiles. In our study five out of seven children with ADHD clustered together with those with milder speech and language symptoms, suggesting that comorbid ADHD is not necessarily associated with a more severe speech and language disorder.…”
Section: Cas Co-occuring With Complex Neurodevelopmental Disordersmentioning
confidence: 99%
“…Isolated CAS seems to account for only a part of the cases, while children with complex comorbid profiles represent a large population with different needs in terms of diagnosis, healthcare, treatment and educational support [23]. Furthermore, the co-occurrence of CAS and language impairment (LI) is frequently documented in literature [4,6,[22][23][24][25]. In English-speaking children with CAS, some authors described [24,26] the presence of morphological errors that were not entirely explained by the motor speech deficits, thus suggesting a possible linguistic origin.…”
Section: Introductionmentioning
confidence: 99%